Optimalisasi Perilaku Hidup Bersih dan Sehat Santri Melalui Intervensi Edukatif dan Fasilitasi Kesehatan di Pondok Pesantren As Shomadiyah Kabupaten Bangkalan - Reswari, Putu Ayu Dhana; Amalia, Yustisia; Widuri, Sasi; Kwarta, Cityta Putri; Kusumawardani, Lentera Afrida (Health Care : Journal of Community Service, 2025)
This community service program aims to improve the implementation of Clean and Healthy Living Behaviors (PHBS) among students at the As Shomadiyah Islamic Boarding School in Bangkalan Regency, through educational interventions and health facilitation. The activities were implemented using interactive counseling methods, demonstrations of personal hygiene practices, and the provision of supporting facilities such as handwashing stations, soap, and educational posters. Before the intervention, most students had not consistently implemented PHBS, particularly regarding proper handwashing, maintaining environmental cleanliness, and waste management. After the program, there was an 80% increase in students' knowledge and skills related to PHBS, based on pre- and post-test results. Furthermore, observations showed increased compliance with maintaining personal and environmental hygiene. This program demonstrated that an educational approach combined with the provision of health facilities is effective in optimizing clean and healthy living behaviors within the Islamic boarding school environment. This activity is expected to serve as a model for sustainable health development that can be replicated in other Islamic boarding schools.